Drinking Water Quality in an Induction Camp at Oyo State, Nigeria: A Preliminary Assessment - John B. Edet; Nnanake-Abasi O. Offiong; Akwaowo I. Inyangudoh; Idorenyin E. Moses; Emediong N. Ntukidem; Faith M. Umah; Owen P. Ukafiaf (Archives of Current Research International, 2016)
Physicochemical and microbial characterization of a groundwater source in an induction camp sited in Oyo state, Nigeria was conducted between April, 2016-June, 2016, to determine its fitness for drinking using standard analytical methods. The water quality index derived mainly from the physicochemical parameters revealed that drinking water samples were of poor quality. Total heterotrophic counts were found to be within the range of (16-70) x102 CFU/ml and (15-75) x102 CFU/ml before and after the orientation exercise respectively, which were above the recommended standard of 5x102 CFU/ml for treated water as specified by United States Environmental Protection Agency (USEPA). Total coliform was observed to be positive only at some sampling points. Escherichia coli and Staphylococcus aureus were also isolated at sampling points P1 and P2 (6 CFU/ml and 1 CFU/ml respectively). No fungal and Salmonella-Shigella organisms were observed in all the samples. The results revealed that it is necessary to improve on the treatment technique for the drinking water source and also advice participants on the need to maintain adequate hygiene during camping period.